Vegetable oil−ionic liquid-based emulsion liquid membrane for the removal of lactic acid from aqueous streams: emulsion size, membrane breakage, and stability study - Khan, Huma Warsi; Elgharbawy, Amal A.M.; Bustam, Mohamed Azmi; Goto, Masahiro; Moniruzzaman, Muhammad (American Chemical Society, 2022)
In this study, we present a highly stable vegetable oil ionic liquid (IL)-based emulsion liquid membrane (VOILELM) for the removal of lactic acid from water streams. The system developed as a part of this work comprises a non-ionic surfactant Span 80, sodium hydroxide as an internal stripping agent, sunflower canola oil as a green diluent, and ILtetramethylam- monium acetate [TMAm][Ac]as a carrier. VOILELM stability was evaluated in terms of breakage, emulsion diameter, and standalone stability. The effect of various parameters, namely, concentration of the surfactant, concentration of the internal stripping agent, concentration of the carrier, phase ratio, homogenizer speed, and homogenization time, on the VOILELM stability was studied. The results revealed that VOILELM was highly stable, with 1.34% minimum breakage, 1.16 μm emulsion diameter, and 131 min standalone stability. The optimal process parameters were 0.1 wt % Span 80, 0.1 M NaOH, 0.3 wt % IL, 0.25 phase ratio, 5000 rpm homogenizer speed, and 5 min homogenization time. At these optimized conditions, 96.08% lactic acid extraction efficiency was achieved. Thus, a highly effective VOILELM was developed, with minimal breakage and emulsion diameter and maximum stability.